Bleeding Events in Thrombocytopenic Patients With Cancer Undergoing Acute Rehabilitation. Issue 1 (22nd March 2018) - Neal, Jacqueline; Shahpar, Samman; Spill, Gayle; Semik, Patrick; Marciniak, Christina
Objectives: To determine incidence of bleeding in thrombocytopenic patients with cancer undergoing acute inpatient rehabilitation. Design: This is an observational cross-sectional retrospective study. Setting: Acute inpatient academic rehabilitation facility. Participants: Adult patients admitted to acute inpatient rehabilitation with functional impairments secondary to cancer. Methods: Electronic records were reviewed for thrombocytopenic patients with cancer to determine platelet counts, bleeding events during rehabilitation, and anticoagulant medications prescribed. Main outcomes measurements: Type and number of bleeding events, severity of bleeding by World Health Organization criteria. Results: Of the 278 patients with cancer admitted to acute rehabilitation over a 27-month time frame, 119 had at least one platelet count <150 000/µL. In all, 37 (31.1%) had a history of a bleeding event prior to the rehabilitation admission and 34 (28.6%) had at least one bleeding complication during their stay. Most events (87.5%) were of low grade (Grade 1 and 2 World Health Organization criteria). There was no association between platelet counts <11 000 or counts 11 000 to 20 000/µL and the occurrence of bleeding ( P = .106 and P = .319, respectively). Although anticoagulants were common, there was no association found with a bleeding event and either anticoagulation status (receiving or not on such agents), specific anticoagulant or antiplatelet agents, or a combination. Conclusions: Bleeding events in patients with cancer with thrombocytopenia during acute rehabilitation stay are not uncommon but are typically mild in severity and not associated with the degree of thrombocytopenia. Patients taking anticoagulants when platelet levels rose did experience bleeding events, but not at a statistically greater rate than those not taking such medications.